A novel flavonoid with antioxidant activity from Patrinia villosa (Thunb.) Juss. Issue 12 (15th June 2022) - Liu, Yang-Cheng; Sui, Nan; Wang, Jia-Qi; Wang, Xin; Liu, Wei; Xiang, Zheng; Chen, Chang-Lan
Abstract: Patrinia villosa (Thunb.) Juss ( P. villosa ), a perennial herb, is widely used as a medicinal plant in Chinese folk. This study aims to isolate and identify the chemical constituents from P. villosa and evaluate their antioxidant activity. Normal silica column chromatography, ODS silica column chromatography, Sephadex LH-20 column chromatography and semi-preparative HPLC methods were used to obtain a new compound named 3-n-pentadecyl-4'-methoxyluteolin (1) and two known compounds including luteolin-7-O-β-D-glucuronide methyl ester (2) and apigenin-7-O-β-D-glucuronide methyl ester (3). The antioxidant activity of these compounds was determined by DPPH and ABTS methods and the IC50 values were calculated. The IC50 values of ABTS scavenging activity of 1, 2 and 3 were 12.99 ± 0.09 μM, 7.13 ± 0.07 μM and 5.15 ± 0.08 μM, respectively, and the IC50 values of DPPH scavenging activity of 1, 2 and 3 were 51.86 ± 0.41 μM, 23.95 ± 0.71 μM and 25.06 ± 0.65 μM, respectively. All the compounds exhibited good antioxidant activities in vitro. Graphical Abstract: UF0001